Investigation of burr formation in micro end milling - Ali, Mohammad Yeakub; Alif, M.; Irman, K.; Hajar, N.; Hayati, N. (2008)
This paper discussed the investigation of the burr formation in micro end milling process on stainless steel. Thus, formation of burr after machined by micro end milling process was investigated and analyzed. Tungsten carbide end mill cutting tool of diameter 500 μm was used with depth of cut of 200 μm. A number of microchannels were machined to characterize the process parameters that influenced the burr formation of micro end milling process. Two-level three-factor of experiments were developed to predict the burr height. Experiments were conducted with two process parameters: feed per tooth and cutting speeds. Heights of the burrs with different condition of parameters were measured. Burr height was found to be linearly proportional to feed per tooth and cutting speeds. Elimination of the burrs from the microchannel surface would give a good geometric accuracy which it can be used for microfluidic analysis.